2016
DOI: 10.4038/engineer.v49i1.6915
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salinity on Mechanical Behaviour of Well Cement: Application to Carbon Capture and Storage Wells

Abstract: Integrity of injection wells play a vital role in the success of carbon capturing storages (CCS) and oil/gas extraction projects. Well cement plays a vital role in ensuring well integrity and the loss of well integrity may be caused due to the down-hole curing conditions. The salinity in the storage reservoirs varies from 0-30% NaCl depending on the geological location, and hence a typical well cement is exposed to a range of salinity levels. Therefore, aim of this research was to analyze the mechanical behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 3 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…Gowthaman et al [7] Constituents OPC based well cement (%) Neat well cement samples (without any aggregate) were prepared with a diameter of 40 mm and a height 80 mm using PVC moulds. The water/cement (w/c) ratio used in the sample preparation was 0.44 as it has been found that this is the optimum water cement ratio that will get the maximum strength [8,10,11].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gowthaman et al [7] Constituents OPC based well cement (%) Neat well cement samples (without any aggregate) were prepared with a diameter of 40 mm and a height 80 mm using PVC moulds. The water/cement (w/c) ratio used in the sample preparation was 0.44 as it has been found that this is the optimum water cement ratio that will get the maximum strength [8,10,11].…”
Section: Methodsmentioning
confidence: 99%
“…Already, a few studies [7,8,9,12,16] focusing on the behaviour of well cement of oil wells under different temperature and salinity conditions have been done. Xingshan et al [16] have conducted a research using high sulphate resistance Class G cement slurry with a w/c ratio of 0.44 to study the effect of salt content on the properties of cement slurry and on the hydration process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the retardation of hydration as well as the degradation of C-S-H, the strength will reduce with salinity level. It was ensured that the white colour crystals in Figure 9-1 (b and C) are CaCl 2 solid deposits as it has been found that CaCl 2 will get formed when OPC is cured in brine water [11]. From the microstructure of the geopolymer, it can be seen that the particles are packed loosely and that large voids and a fibrous surface (Figure 9-2(d)) are formed when the structure is cured in plain water (0 % NaCl).…”
Section: Engineermentioning
confidence: 99%
“…They have observed that the strength of geopolymer reduces with the curing period and that the rate of reduction of strength reduces as the brine concentration is increased with the high salt content in the brine solution offering resistance to alkali leaching. Gowthaman et al [11] studied the mechanical behaviour of Class G cement for different curing periods (7, 14, 28 and 45 days) at different salinity levels (0 %, 10 %, 20 % and 30 %) and at an average temperature of 50 °C. They have concluded that the retardation of hydration causes the strength of Class G cement to reduce as the salinity level is increased and that the hydration process will cause the strength to increase with the curing period.…”
Section: Introductionmentioning
confidence: 99%